Active deformation delineated by geomorphic and sedimentary response of rivers, central Zagros fold – thrust belt, SW iran - Amanipoor, Hakimeh (Geodesy and Cartography, 2015)
The mountain generation in Iran is because of continental collision between the Arabian and Eur-asia plate. Southwestern Iran shows active shorten that its evidences is deformation of crust and frequent earthquakes. At depth, active basement of the Zagros fold-thrust-belt in southwestern Iran, which are covered by folding of the Phanerozoic sediments, affected by some blind thrusted faults that have seismic nature. The Zagros fold-thrust-belt can be divided into 4 lithotectonic units including Sanandaj-Sirjan Zone (SSZ), Imbricate Zone (IZ), Zagros Fold Belt (ZFB), and Molasse Cover Sequence (MCS); this dividing and classification is based on geomorphology landscape, drainage pattern, rate of tectonics and stratigraphic records. Each tectonic unit characterized by especial abnormal forces in river systems. Active tectonics has the most important role to control the river systems by changing of channels incline. Change in the drainage pattern, channels cut, longitudinal profile, anomalous changes of sinuosity, changing of the side form and forming of terrace, change of river direction, compact meanders, cutting of meanders and geomorphology features of the rivers are responds to the active tectonics of region that are studied using remote sensing, DEM and field observations. These parameters are used to understand the vertical movement in the study area. Existing structures, especially growing anticlines and blind thrusted faults in the Zagros fold-thrust-belt, which cut the river channels and sometimes put them in parallel, are used in the study of their effect on the longitudinal and transverse tilt of morphological changes.